Developments in fabrication properties and applications of light weight high entropy alloys - Pradyumn Kumar Arya; Dan Sathiaraj; Vinay Kumar Patel; Kuldeep K. Saxena; Deepak Kumar Soni; C. Rakesh; M. Ijaz Khan (Results in Engineering)
Lightweight high-entropy alloys (LWHEAs) belong to the class of advanced alloys that constitute various primary components in equiatomic or near-equiatomic proportions. LWHEAs have attracted the researchers' attention to meet the stringent requirements of aerospace, automotive, and other high-performance sectors. This review outlines the critical objectives of developing LWHEAs: achieving high strength-to-weight ratios, excellent thermal stability, and enhanced resistance to wear, corrosion, and oxidation. It highlights recent advancements in fabrication strategies, including casting, powder metallurgy, and additive manufacturing. Al and Ti-based LWHEAs have been extensively researched and most widely studied, and it has been revealed that the body-centered cubic (BCC) solid solution phase might be the most prominent one. The current review article details the various fabrication methodologies and their derived properties, formation mechanisms of complex phases, role of entropy in phase stability, and novel applications in extreme environments. Key research directions are identified to guide future exploration toward cost-effective, low-density, and thermally stable alloy systems.